Pengaruh Brand Image, Brand Awarenees, Service Quality, dan Digital Banking terhadap Loyalitas Nasabah melalui Kepuasan Nasabah sebagai Variabel Intervening (Studi pada Nasabah Bank Syariah Indonesia KCP Ungaran Diponegoro 1): The Influence of Brand Image, Brand Awareness, Service Quality, and Digital Banking on Customer Loyalty through Customer Satisfaction as an Intervening Variable (Study on Customers of Bank Syariah Indonesia KCP Ungaran Diponegoro 1) - Dina Irmawati; Mochlasin Mochlasin (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2026)
Purpose: This study aims to examine the effects of brand image, brand awareness, service quality, and digital banking on customer loyalty through customer satisfaction as a mediating variable among customers of BSI KCP Ungaran Diponegoro 1. Design/methodology/approach: This study uses a quantitative approach with primary data collected through questionnaires. The data were analyzed to examine both direct and indirect effects among the research variables. Research Findings: The findings show that brand image and service quality do not have a significant direct effect on customer loyalty. In contrast, brand awareness and digital banking have a positive and significant effect on customer loyalty. Customer satisfaction also has a positive and significant effect on customer loyalty. Furthermore, customer satisfaction does not mediate the effect of brand image on customer loyalty, but it mediates the effects of brand awareness, service quality, and digital banking on customer loyalty. Contribution/Originality/Novelty: This study provides empirical evidence on the determinants of customer loyalty in Islamic banking at the branch level, particularly at BSI KCP Ungaran Diponegoro 1. The findings highlight the importance of brand awareness and digital banking as key drivers of loyalty, while also emphasizing the role of customer satisfaction as a mediating mechanism in strengthening long-term customer loyalty